2002
DOI: 10.1099/0022-1317-83-7-1771
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of a single amino acid in the 2b protein of Pea early-browning virus affects nematode transmission

Abstract: The 2b protein of Pea early-browning virus (PEBV) is required for transmission of the virus by nematodes. Comparison of the 2b proteins of highly transmissible (TpA56) and poorly transmissible (SP5) isolates of PEBV identified two amino acid substitutions (G90S and G177R) that might be responsible for the poor transmission of isolate SP5. Hybrid viruses were created in which the TpA56 2b protein carried SP5-specific substitutions at residue 90 or 177, and in which the SP5 2b protein carried TpA56-specific subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Tobravirus RNA2 is variable in size and, as well Harrison et al (1974) and panel (B) from Wang and Gergerich (1998) (Vellios et al, 2002a;MacFarlane, 2003;Holeva and MacFarlane, 2006). Changing amino acid 177, which lies in a predicted coiledcoil domain in PEBV 2b protein, controls nematode transmissibility (Vellios et al, 2002b). It is suggested that this coiled-coil might mediate the interaction between 2b and CPs.…”
Section: B Tobravirusesmentioning
confidence: 78%
“…Tobravirus RNA2 is variable in size and, as well Harrison et al (1974) and panel (B) from Wang and Gergerich (1998) (Vellios et al, 2002a;MacFarlane, 2003;Holeva and MacFarlane, 2006). Changing amino acid 177, which lies in a predicted coiledcoil domain in PEBV 2b protein, controls nematode transmissibility (Vellios et al, 2002b). It is suggested that this coiled-coil might mediate the interaction between 2b and CPs.…”
Section: B Tobravirusesmentioning
confidence: 78%
“…For Cauliflower mosaic virus (CaMV; genus Caulimovirus, family Caulimoviridae), a single amino acid change in protein P2, which acts as HC, is sufficient to abolish aphid transmission (24). In the case of nematode-transmitted viruses, a single mutation in the HC protein 2b of Pea early-browning virus (PEBV; genus Tobravirus, unassigned family) is sufficient to prevent transmission (38). Similarly, a 15-amino-acid deletion at the C terminus of the CP abolishes transmission of PEBV (22).…”
mentioning
confidence: 99%
“…The PepRSV RNA 2 segment is 1799 bases long and encodes only the coat protein (CP) gene (NC_003670). However, the RNA 2 of TRV and PEBV additionally encodes one or two nonstructural proteins (2b and 2c) [11][12][13][14], which are involved in nematode transmission [12, [15][16][17][18].…”
Section: Pepper Ringspot Virus (Peprsv) Is a Member Of The Genusmentioning
confidence: 99%